Evaluation of Waste Bank Program: Transformative Impact on Community Welfare, Environment, and Economy - Irfana, Tungga; Harjono, Rosita; Diana, Tungga (Research Horizon, 2023)
This research addresses the pressing challenges of waste management in the context of population growth, economic shifts, and changing consumption patterns. Emphasizing the need for a paradigm shift in perceiving waste as valuable, the study advocates for holistic waste reduction involving government, businesses, and the public. Focusing on waste bank programs in Indonesia, particularly the Wijaya Kusuma Waste Bank in Bekasi, West Java, the research evaluates their impact on community empowerment, environmental preservation, and economic improvement. The study employs a qualitative approach and the Context, Input, Process, and Product (CIPP) evaluation model to assess the waste bank program comprehensively. The results highlight the existing conditions of the Wijaya Kusuma Waste Bank, its objectives, and the community's response. The waste items deposited by customers are categorized for effective management. A comprehensive evaluation explores the legal basis, human resources, and funding aspects, revealing strengths and areas for improvement. The waste bank program's transformative potential is discussed, emphasizing its positive impact on social, economic, and environmental dimensions within the Griya Persada Elok community. The conclusion underscores the commendable success of the Wijaya Kusuma Waste Bank, outlining the need for continued support, organizational enhancements, and strategic planning to ensure sustained positive outcomes and serve as a model for community-driven environmental initiatives.